Adaptation to environmental stress in the lone star tick, Amblyomma americanum: osmoregulation, thermoregulation, and microbiome - Maldonado-Ruiz, Lucia Paulina (Kansas State University, 2021)
Ticks are the arthropod vectors with the widest range of harbored pathogens. Ticks can survive for extended periods of time, often more than a year, without dietary nutrition during their off-host periods under stressful environmental conditions. In addition, during the time, ticks can maintain water balance in dry environment. Here, we report that the lone star ticks, Amblyomma americanum, can actively drink water, which greatly increases their survival rates. Significance of the ticks drinking environmental water is brought up in this study; importance of direct water drinking in the tick survival and implications of the water drinking in acquisition of environmental organic and inorganic constituents. In the Chapter 2, I found that ticks directly drinking water is necessary for their survival. It was also demonstrated that ticks drinking certain inorganic components or a bacterium leads to tick death, which offers a new avenue for tick management by the delivery of toxic agents through drinking water. Tick water homeostasis physiology was further expanded to the study of the dermal secretion physiology and its relevance in terms of thermoregulation and dehydration in Chapter 3. Dermal secretion, analogous to the vertebrate sweat, occurs through type II dermal glands located under the cuticle layer, which are exclusive to Metastriate ticks, including Amblyomma. In this research, I found that contact of a heat probe on the tick body can induce the secretory response. The dermal secretion was induced at as low as 35°C, while an exhaustive dermal secretion induced by 52°C resulted in tick lethality in 24-hour. We demonstrated that a role of dermal secretion is evaporative cooling that shortens the time for cooling the body 1-1.2 seconds faster than those of the ticks which did not secrete. In a further in depth study for understanding the mechanisms of the secretion, I found that the dermal secretion is triggered by serotonin. Ouabain, Na/K-ATPase blocker, suppresses the serotonin-mediated dermal secretion. A candidate serotonin receptor mediating the dermal secretion was identified as A. americanum serotonin receptor 1A (Aame5-HT1A) in a transcriptomics study. The study for understanding the impacts and potential applications of environmental water drinking physiology was further expanded to a microbiome of A. americanum females collected in eastern Kansas in Chapter 4. The 16S rRNA sequencing results showed the dominant endosymbiotic genera Coxiella and Rickettsia (>95%) with other operational taxonomic units (OTUs) presenting typical soil bacterial taxa, implying that the environmental bacteria are frequently acquired by the tick, presumably, through the water drinking. This study has uncovered the physiological mechanisms that expose a vulnerable tick physiology that can be targeted in development of tick control measures. Delivery of tick-specific toxic reagent disrupting the osmoregulation or pathogenic agents inducing bacterial dysbiosis may provide new routes for development of tick management strategies.
Keywords: Ticks; Drinking; Tick management; Liquid water; Evaporative cooling; 16S rDNA